2019
DOI: 10.1055/s-0039-1695017
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play after Anterior Cruciate Ligament Reconstruction among Amateur Soccer Players

Abstract: Objective The aim of the present study is to assess the return to play among amateur soccer league players after anterior cruciate ligament (ACL) reconstruction. Materials and Method The surgical protocols of ACL reconstruction surgeries performed in a sports medicine clinic from July 1st, 2013, to June 30th, 2014, were included in the study. Only the charts of amateur soccer league players who played once or twice a week were selected. The follow-up time was calculated as the number of months betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…All discrepancies were resolved following consultation with the first author (MM). In terms of study design, there were six cohort studies [30,32,38,40,44,45], five case series [29,31,33,34,37], three case-control studies [39,42,43], two prospective cohort studies [35,36], and one descriptive epidemiology study [41], and level II [35,36], level III [30,32,[38][39][40][41][42][43][44][45], and level IV [29,31,33,34,37] of evidence were recorded. Level II evidence refers to prospective cohort studies, level III of evidence refers to case-control and cohort studies, while level IV evidence refers to case series.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…All discrepancies were resolved following consultation with the first author (MM). In terms of study design, there were six cohort studies [30,32,38,40,44,45], five case series [29,31,33,34,37], three case-control studies [39,42,43], two prospective cohort studies [35,36], and one descriptive epidemiology study [41], and level II [35,36], level III [30,32,[38][39][40][41][42][43][44][45], and level IV [29,31,33,34,37] of evidence were recorded. Level II evidence refers to prospective cohort studies, level III of evidence refers to case-control and cohort studies, while level IV evidence refers to case series.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Athletes most commonly competed in the prestigious European soccer leagues, including England, France, Germany, Italy, Spain, Portugal, and Belgium, but also in the United States, Australia, and Chile. Ten [30-33, 35, 37, 38, 41, 42, 44] out of 17 investigations examined elite soccer players exclusively, whilst there were also national-level [36,43], amateur [29,45], recreational [40,43], and youth athletes [36,40,43]. Concerning ACLR, in nine studies, soccer players underwent both primary and revision of ACLR [32,33,35,36,38,[42][43][44][45].…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the articles that were included in the review were of Level 3 to 4 evidence; 1 of 32 (3.1%) was Level 1 evidence, 44 11 of 32 of studies were Level 2, 2,5,6,9,10,14,20,24,64,75,77 11 of 32 (34.4%) of studies were Level 3 evidence, 1,3,21,22,24,25,52,54,60,61,71 and 9 of 32 (28.1%) of studies were Level 4 evidence. 4,12,33,35,38,58,62,74,80 The outcomes of 3112 soccer players after ACLR were available for analysis. The reported number of male athletes who underwent ACLR was 1780, compared with 1181 female athletes (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The range of mean age of soccer players who underwent ACLR was 15.7 to 29.7 years, range of mean height was 1.68 to 1.82 m, and range of mean BMI was 22.8 to 24.9 kg/m 2 . Of the studies that reported the type of graft used for the reconstruction, 14 of 32 (43.8%) studies used autografts 1,[3][4][5]9,14,20,33,38,44,54,60,64,74 ; the 2 most commonly used grafts included 1600 hamstring tendon (HT) and 663 bone-patellar-tendon-bone (BPTB) grafts. Using the concomitant procedures data, the range of patients with articular cartilage involvement was 6.5% to 30.4% and meniscal involvement was 35.6% to 60.0% (Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%